The fight against systemic corruption: lessons from Brazil (2013-2022) - Trombini, Maria Eugenia; Valarini, Elizângela; Oliveira, Vanessa Elias de; Pohlmann, Markus (Organization, Management and Crime - Organisation, Management und Kriminalität, 2024)
This open access book examines the interplay between public and private sectors in Latin America's biggest market. It is the result of the binational research project “Organizational Crime and Systemic Corruption in Brazil” funded by the DFG and FAPESP (2018-2023). Its contributions analyze anticorruption, political finance, and how for-profit organizations manage illegality. The Editors Dr. Maria Eugenia Trombini is a Post-doctoral researcher at the Heidelberg Center for Ibero-american Studies. Her PhD research "Legal Professionals in White-Collar Crime: Knowing, Thinking and Acting" won the 2023 Dr. Gerhard-Ott Price and has been published by Springer. Dr. Elizangela Valarini was a Postdoctoral Scholar at the Max Weber Institute at Heidelberg University. She coordinated the binational project from the German side and organized this collected volume prior to joining SAP in 2022. Prof. Dr. Vanessa Elias de Oliveira is Professor of Political Science at the Federal University of ABC and a member of the Public Policies graduate program whose research focuses on Judicial Institutions. Prof. Dr. Markus Pohlmann is Professor of Sociology at Heidelberg University, where he leads the Heidelberg Research Group for Organization Studies. He has conducted studies on wrongdoing by companies and public entities and is the main Editor behind this book series.